PENERAPAN ASAS NASIONALITAS AKTIF TERHADAP TINDAK PIDANA PENCUCIAN UANG - Ni Putu Ari Setyaningsih (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
Money laundering crime is a follow-up crime which is forwarded from a predicate crime. In line with technological developments, the proceeds of criminal offenses that are laundered may also come from the proceeds of crimes committed outside the territory of Indonesia. Money Laundering Act stipulates that the predicate crime of money laundering committed outside the territory of Indonesia can be prosecuted and tried under Indonesian law as well as Indonesian citizens who are outside the territory of Indonesia who participate in conducting trials and assistance. or a malicious consensus to commit the crime of laundering. However, the application of Indonesian law to crimes committed in the territorial areas of other countries will relate to issues of law enforcement jurisdiction. This raises a problem regarding the extent to which the active nationality principle can apply to the perpetrators of the crime of money laundering whose predicate crime and crimes of probation, co-operation or conspiracy are committed outside the territory of Indonesia. The preparation of this paper uses a normative research method with a statutory approach. This paper concludes that the active nationality principle can be applied based on the provisions of Article 2 paragraph (1) letter z and Article 10 of the Money Laundering Act. The application of the active nationality principle cannot be carried out absolutely because there are limitations related to the sovereignty of the State where the criminal act is committed, the sovereignty of this country is closely related to the legal jurisdiction of a country. Therefore, to be able to apply Money Laundering Act in the jurisdiction of other countries, a legal basis is needed in the form of formal cooperation or mutual assistance. In addition, a technical extradition treaty is required to hand over the perpetrator of a criminal offense to the Indonesian state.